Refractive and biometric status of children born premature without retinopathy of prematurity - Sharanjeet-Kaur,; Norlaila Mat Daud,; Chung, Kah Meng; Azrin E. Ariffin,; Boo Nemyun,; Ong, Lai Choo (Universiti Kebangsaan Malaysia, 2010)
A cross-sectional study was undertaken to determine the refractive and biometric status of premature children without Retinopathy of Prematurity (ROP) and full term children. Fifty eight children between the ages of 3 and 7 years (32 children born premature without ROP and another 26 children born full term and normal) were examined. Refractive error, corneal curvature, axial length, anterior chamber depth and crystalline lens thickness were determined. The results revealed that children between the age of 3 years and 7 years were emmetropic, irrespective of whether they were born premature without ROP or full term. However, children born premature without ROP had significantly steeper corneas (t = 3.14, p = 0.0349), shorter axial lengths (t = 3.18, p = 0.0313) and thicker crystalline lens (t = 3.31, p = 0.0256) compared to children born full term within the same age group. This study suggests that compensation in ocular parameters can occur to maintain emmetropia, mainly by adjustment of axial length and corneal curvature.